Changes of Impedance Audiometry before and after Adenoidectomy in a Clinically Normal Ear (Bangladesh Journal of Otorhinolaryngology, 2022)
Background: The nasopharyngeal tonsil, universally known as adenoids is to be found at the crossroads of roof along with posterior wall of nasopharynx. Adenoid is gift next to birth. Adenoid mass may block the eustachian tube, retracted tympanic membrane leads to conductive hearing loss. Impedance audiometry helps to assess the condition.Objective: To observe the changes of impedance audiometry before and after adenoidectomy in a clinically normal ear.Methods: This longitudinal study was done in Cumilla Medical College & Hospital, Cumilla during a period of one year. 50 Cases of enlarged adenoids of 3-12 years admitted in ENT ward were included in this study. All cases underwent adenotonsillectomy. Impedance Audiometry was done before and one month after adenotonsillectomy. Collected data were classified, edited, coded and statistical analysis was done.Results: Total 50 cases, mean age was 6.95(±1.77) years. Majority 33(66%) were male and 17(34%) were female. Middle ear pressure of both ears was increased after adenotonsillectomy. After operation 40(80%) was type A curve and 09(18%) was type B in right ear and 42(84%) was type A curve and 08(16%) was B curve in left ear.Conclusion: Majority tympanometry was type B in both ears before adenotonsillectomy and after operation majority tympanometry curvature was type A in both earsBangladesh J Otorhinolaryngol 2022; 28(1): 62-67